MECHANISMS OF FORMATION OF ETHNO-PEDAGOGICAL VALUES IN STUDENTS OF PEDAGOGICAL HIGHER EDUCATION INSTITUTIONS - Rayimov , Begali Uralovich (Educational Research in Universal Sciences, 2023)
The pedagogical and psychological aspects of ensuring the activity of preschool children as a subject have been improved on the basis of determining the speed, level, way of thinking, taking into account the gender characteristics of children (thinking, speech development, movement speed, cognitive ability); Preparatory groups in preschool educational organizations have defined the conditions for activating educators’ logical and creative thinking by using elements of national pedagogy (fairy tale therapy, quick speech, articles, games, folk songs);